KINERJA PT RAPP DALAM PENCEGAHAN KEBAKARAN HUTAN DAN LAHAN MELALUI FIRE FREE VILLAGE PROGRAM (FFVP) DI KECAMATAN MERBAU, KEPULAUAN MERANTI - Koniah "; Harapan Tua RFS (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Disaster land and forest fires are a serious problem that must faced in Riau Province nearly every year during the dry season. as part of efforts to reduce the level of forest fire in the area around PT, PT RAPP units APRIL GROUP Company initiated Fire Free Village Program ( FFVP) which began in 2015. The aim of this study is to explain how the performance of PT RAPP in prevention through FFVP in District Merbau, Meranti Islands. And explain what are the factors supporting PT RAPP performance in the prevention of forest fires and land through FFVP in District Merbau, Meranti Islands. The concept of the theory is the measurement of organizational performance by Muhammad Mahsun in (Lijen Poltak Sinambela, 2016) consisting of: set goals, objectives and strategies, formulate indicators / measures of performance, achievement of the objectives, performance evaluation. The method used is a qualitative research with case study approach, the selection of informants using purposive sampling technique. The technique of collecting data through observation, interviews and documentation. The results of this study explained that the performance of PT RAPP in the prevention of forest fires and land in the District Merbau is optimal, this is evidenced by the level of land and forest fires decreased even within the last 2 years did not fire. it is not independent of the supporting factors such as community participation, budget, socialization and communication. * Keywords :Organizational Performance, Prevention, Programs